Central nervous system vasculitis and pediatric stroke - Taraman, Sharief; Jani-Acsadi, Agnes; Tselis, Alexandros (Journal of Pediatric Neurology, 2010)
This paper reviews the spectrum of vasculitides that affect the brain, specifically focusing on primary angiitis of the central nervous system (CNS) and how they relate to stroke in the pediatric population. CNS vasculitis accounts for a substantial portion of pediatric stroke. The extent and severity of the stroke is variable. Hemiparesis and encephalopathy occur commonly, but are not specific to CNS vasculitis. The non-specific presentation and results of investigations make diagnosis difficult. Lack of controlled treatment trials complicates the management. Blood inflammatory markers, cerebrospinal fluid analysis, multiple imaging techniques including conventional angiography, and brain biopsy form the routine workup. Therapeutic modalities including anti-platelet agents, corticosteroids, cyclophosphamide, and other immunomodulatory agents have been used with the vertical line on the right is cutting into the text apparent success, but the evidence is mostly anecdotal.
Keywords: Stroke; vasculitis; angiitis; central nervous system; pediatric